Survivance in Indigenous Science Fictions: Vizenor, Silko, Glancy, and the Rejection of Imperial Victimry. Issue 1 (2016) - Higgins, David M.
Abstract : In contemporary mainstream science fiction victims are frequently the ultimate heroes, and white men are often (astonishingly) the ultimate victims. To occupy the position of the victim is often to be absolved of guilt and invested with the moral authority of retributive agency, and science fiction repeatedly offers agents of privilege an invitation to occupy the position of victims. In sharp contrast to this embrace of imperial masochism within mainstream science fiction, one of the most striking aspects of indigenous speculative fictions is a consistent refusal to sanctify victimry. Despite centuries of genocidal violence and extraordinary hardship within enduring settler–colonial regimes, indigenous sf narratives deconstruct victimization and eschew imperial masochism in favor of what Gerald Vizenor refers to as survivance paradigms. This essay examines key indigenous science fictions that reject victimization in favor of survivance narratives. Vizenor's own "Custer on the Slipstream" (1978), for example, rejects the American imperial narrative of George Armstrong Custer as a victim–hero and exposes him as an agent of colonial oppression. Vizenor frames resurrection as a literal transmission of imperialist ideologies, and his hero, a reborn iteration of Sitting Bull and/or Crazy Horse, rejects the notion that Indigenous Americans have been defeated in war and reveals that white Americans are corrupted with a self-defeating spiritual sickness. Vizenor's emphasis on spiritual illness mirror's Leslie Marmon Silko's portrayal of "witchery" in Ceremony (1977) and Dianne Glancy's description of deadening cold in "Aunt Parnetta's Electric Blisters" (1990). In both of these narratives, biskaabiiyang is achieved not through embracing the role of victim but rather by rejecting paradigms of oppositional duality in favor of a sacred recognition of alterity and creativity.